Is There Any Association Between Neurodegenerative Diseases and Periodontitis? A Systematic Review - Alvarenga, María Olimpia Paz; Frazão, Deborah Ribeiro; Matos, Isabella Gomes de; Bittencourt, Leonardo Oliveira; Fagundes, Nathália Carolina Fernandes; Rösing, Cassiano Kuchenbecker; Maia, Lucianne Cople; Lima, Rafael Rodrigues (Frontiers in Aging Neuroscience, 2021)
Background: Neurodegenerative diseases are a group of progressive disorders that affect the central nervous system (CNS) such as Alzheimer, Parkinson, and multiple sclerosis. Inflammation plays a critical role in the onset and progression of these injuries. Periodontitis is considered an inflammatory disease caused by oral biofilms around the tooth-supporting tissues, leading to a systemic and chronic inflammatory condition. Thus, this systematic review aimed to search for evidence in the association between neurodegenerative disorders and periodontitis. Methods: This systematic review was registered at International Prospective Register of Systematic Reviews (PROSPERO) under the code CRD 42016038327. The search strategy was performed in three electronic databases and one gray literature source—PubMed, Scopus, Web of Science, and OpenGrey, based on the PECO acronym: observational studies in humans (P) in which a neurodegenerative disease was present (E) or absent (C) to observe an association with periodontitis (O). The Fowkes and Fulton checklist was used to critically appraise the methodological quality and the risk of bias of individual studies. The quality of evidence was assessed by the Grading of Recommendations Assessment, Development and Evaluation (GRADE). Results: From 534 articles found, 12 were included, of which eight were case–control, three were cross-sectional, and one was a cohort, giving a total of 3,460 participants. All the included studies reported an association between some neurodegenerative diseases and periodontitis and presented a low risk of bias. According to the GRADE approach, the level of evidence of probing pocket depth was considered very low due to the significant heterogeneity across the studies' upgrading imprecision and inconsistency. Conclusions: Although all the included studies in this review reported an association between neurodegenerative diseases and periodontitis, the level of evidence was classified to be very low, which suggests a cautious interpretation of the results.